2022
DOI: 10.1038/s41598-022-08397-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new series of quinoline derivatives with insecticidal effects on larval vectors of malaria and dengue diseases

Abstract: Mosquito borne diseases are on the rise because of their fast spread worldwide and the lack of effective treatments. Here we are focusing on the development of a novel anti-malarial and virucidal agent with biocidal effects also on its vectors. We have synthesized a new quinoline (4,7-dichloroquinoline) derivative which showed significant larvicidal and pupicidal properties against a malarial and a dengue vector and a lethal toxicity ranging from 4.408 µM/mL (first instar larvae) to 7.958 µM/mL (pupal populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 78 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…As we discussed earlier, quinoline derivatives possess wideranging therapeutic applications including their extensive usage as antimalarial drugs. [34][35][36] To estimate the binding potency of a few newly synthesized quinoline derivatives, we have docked the selected derivatives 4h, 4n, 4p, 7f and 7g to the chloroquine binding site of the plasmodium falciparum lactate dehydrogenase 37 using AutoDockVina. 38 X-ray crystal structure of the chloroquine binding plasmodium falciparum lactate dehydrogenase (PDB code: 1CET, 2.05 Å) 37 was used as a model system for docking.…”
Section: Synthesis Papermentioning
confidence: 99%
“…As we discussed earlier, quinoline derivatives possess wideranging therapeutic applications including their extensive usage as antimalarial drugs. [34][35][36] To estimate the binding potency of a few newly synthesized quinoline derivatives, we have docked the selected derivatives 4h, 4n, 4p, 7f and 7g to the chloroquine binding site of the plasmodium falciparum lactate dehydrogenase 37 using AutoDockVina. 38 X-ray crystal structure of the chloroquine binding plasmodium falciparum lactate dehydrogenase (PDB code: 1CET, 2.05 Å) 37 was used as a model system for docking.…”
Section: Synthesis Papermentioning
confidence: 99%
“…Quinoline and its derivatives comprise an important group of heterocyclic compounds that exhibit a wide range of pharmacological properties, such as antimalarial (Shiraki et al, 2011;Singh et al, 2011;Murugan et al, 2022), antibacterial (Upadhayaya et al, 2009;Zeleke et al, 2020), antimicrobial (Teja et al, 2016), anti-inflammatory (Guirado et al, 2012), anticancer (Abbas et al, 2015), antidiabetic (Kulkarni et al, 2012) and antihistaminic activities (Sridevi et al, 2010). The quinoline moiety is found in many drugs and is useful in the rational design of novel bioactive molecules in medicinal chemistry.…”
Section: Chemical Contextmentioning
confidence: 99%
“…They have observed that compound 45 exhibited greater activity with IC 50 value 0.005 μg/ml against 3D7 strain type of P. falciparum , as compared with the standard drug chloroquine tested (IC 50 = 0.020 μg/ml; Shah et al, 2012). Murugan et al synthesized a new 4,7‐dichloroquinoline derivative, compound 46 which showed significant in vitro antimalarial activity against both CQ‐resistant ( INDO ) and CQ‐sensitive ( 3D7 ) strains of P. falciparum with IC 50 values of 6.7 and 8.5 nM, respectively (Murugan et al, 2022). Roy et al developed a series of quinolone‐imidazole hybrid compounds, which were tested for blood‐stage antimalarial activity in both drug‐sensitive ( PF3D7 ) and multidrug‐resistant ( K1 ) P. falciparum strains.…”
Section: Biological Activitiesmentioning
confidence: 99%